PENGARUH REKRUTMEN DAN SELEKSI TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH KEJURUAN (SMK) TI BALI GLOBAL DENPASAR - Putu Cindy Candra Dewi; Dewiwati Sujadi (Journal Research of Management, 2020)
School as an educational institution that organize learning activities, really need quality human resources for the success of that school. Which can be done by conducting an effective recruitment and selection process, therefore the school will get qualified teacher which will improve the teacher’s performance in achieving educational goals. Based on the background of the problem in this study, the main problems are as follows: 1) Does recruitment influence teacher performance at TI Bali Global Denpasar Vocational School? 2) Does selection influence teacher performance at TI Bali Global Vocational School Denpasar? 3) How much recruitment and selection influence for teacher performance at TI Bali Global Vocational School Denpasar. The purpose of the research are as follows: 1) To determine the influence of recruitment on teacher performance at TI Bali Global Denpasar Vocational High School 2) To determine the influence of selection on teacher performance at TI Bali Global Vocational High School Denpasar 3) To find out how much influence of recruitment and selection to performance teacher at TI Bali Global Vocational School Denpasar. The population in this study involved all the teacher of TI Bali Global Denpasar Vocational High School amounted 60 people and this study used the population as a sample. The analysis technique used is descriptive analysis, data quality test, classic assumption test, multiple linear regression analysis, t-test analysis and analysis of determination. The results of the analysis show a regression model Y = 3.944 + 0.402 (X1) + 0.470 (X2). The conclusion obtained is that recruitment (X1) partially has a positive and significant effect on teacher performance (Y) on TI Global Global Denpasar Vocational School as indicated by the coefficient b1X1 : tcount = 2.582> ttable (0.05: 57 ) = 1.672 and Sig.t = 0.012 (p <0.05). Selection (X2) partially has a positive and significant effect on teacher performance (Y) on TI Bali Global Denpasar Vocational School, this can be seen in the coefficient b2X2: tcount = 2.994> ttable (0.05: 52 ) = 1.672 and Sig.t = 0.002 (p <0.05). The influence of recruitment and selection on teacher performance at TI Bali Global Denpasar Vocational School is 70.3% while the remaining 29.7% is influenced by other variables outside of this study such as motivation, workload, work environment and others.